2021
DOI: 10.1155/2021/9915921
|View full text |Cite
|
Sign up to set email alerts
|

An Automatic Measurement Method of Test Beam Response Based on Spliced Images

Abstract: Information such as cracks and deflections is the important basis for structural safety. Existing methods have not achieved simultaneous detection. In most existing computer vision measurement systems, the view is fixed due to the fixed position of the camera. Thus, it is difficult to obtain the structures’ overall crack and deflection information. An automatic response measurement method is proposed in this study including ( 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…By deploying sensors and connected devices, civil engineers can gather real-time data on structural health, traffic conditions, and environmental factors, enabling proactive maintenance and more efficient resource allocation for improved safety and sustainability in the field. The authors in study [23] proposed an automatic response measurement method for detecting cracks and deflections in structures. The existing methods lack simultaneous detection of these parameters.…”
Section: The 4ir's Legacy On Civil Engineering: Innovation Infrastruc...mentioning
confidence: 99%
See 1 more Smart Citation
“…By deploying sensors and connected devices, civil engineers can gather real-time data on structural health, traffic conditions, and environmental factors, enabling proactive maintenance and more efficient resource allocation for improved safety and sustainability in the field. The authors in study [23] proposed an automatic response measurement method for detecting cracks and deflections in structures. The existing methods lack simultaneous detection of these parameters.…”
Section: The 4ir's Legacy On Civil Engineering: Innovation Infrastruc...mentioning
confidence: 99%
“…Additionally, it aids in injury prevention and treatment, ensuring athletes reach their full potential while staying safe, serving as a multifaceted asset in the athletic world [36]. In a recent study [37] comparing bionic hands to customized body-powered technology in a demanding work setting, the findings revealed that the customized body-powered arm surpasses the iLimb system in terms of reliability, comfort, efficiency, power, and precision, with significantly reduced maintenance requirements. This research underscores the practical advantages of tailored solutions in prosthetic technology, offering a more dependable and user-friendly alternative in demanding applications.…”
Section: The 4ir's Legacy On Mechanical Engineering: Mechanization Mo...mentioning
confidence: 99%
“…The image stitching algorithm is the key to achieving this operation. In recent years, scholars at home and abroad have put forward many improvement schemes on the basis of traditional image stitching [1][2][3][4][5] . However, the backlight used in the detection of automobile longitudinal beams will ignore its surface information, which makes it difficult to use feature points for stitching operations.…”
Section: Introductionmentioning
confidence: 99%